LAS EXPECTATIVAS ACÁDEMICAS DE LOS ESTUDIANTES PARA POSTULAR EN EL EXAMEN DE ADMISIÓN EN UNIVERSIDADES PERUANAS - Walter Francisco Deza Loyaga (2024)
The present study began with a systematic review of similar studies that served as the basis for developing the data collection instrument, the method to be used was to apply a face-to-face survey to the students in the classrooms of the pre-university high school in the months of January and February of the summer 2023 cycle, through direct observation, the survey was taken from a work sample of 65 students in two classrooms, for this the following research questions were raised that are intended to be answered in the present work: What are the influence of the factors Institutional, social and demographic factors at the time of choosing to study at an Arequipa university?, where it was obtained that they agree for institutional factors (77%), social factors (79%) and demographic factors (75%). From the control questions, the following were obtained: average age (17 years), sex (65% male, 35% female), school of origin (55% national, 38% private and 7% others), socioeconomic level they responded belonging to (Levels A: 0%, B: 21%, C: 63%, D: 11% and E: 5%). From the research it is concluded that academic expectations are related to the academic quality offered by Peruvian universities